Repeat length increases disease penetrance and severity in C9orf72 ALS/FTD BAC transgenic mice - Pattamatta, Amrutha (Hum Mol Genet, 2020)
C9orf72 ALS/FTD patients show remarkable clinical heterogeneity, but the complex biology of the repeat expansion mutation has limited our understanding of the disease. BAC transgenic mice were used to better understand the molecular mechanisms and repeat length effects of C9orf72 ALS/FTD. Genetic analyses of these mice demonstrate that the BAC transgene and not integration site effects cause ALS/FTD phenotypes. Transcriptomic changes in cell proliferation, inflammation and neuronal pathways are found late in disease and alternative splicing changes provide early molecular markers that worsen with disease progression. Isogenic sublines of mice with 800, 500 or 50 G(4)C(2) repeats generated from the single-copy C9–500 line show longer repeats result in earlier onset, increased disease penetrance and increased levels of RNA foci and dipeptide RAN protein aggregates. These data demonstrate G(4)C(2) repeat length is an important driver of disease and identify alternative splicing changes as early biomarkers of C9orf72 ALS/FTD.